Building inclusion and resilience in students with and without SEN through the implementation of narrative speech, role play and creative writing in the mainstream classroom of primary education. Issue 12 (2nd December 2018) - Vitalaki, Elena; Kourkoutas, Elias; Hart, Angie
ABSTRACT: Based on the theory of inclusion, the present 3-year pilot program (2013–2016) deals with narrative speech, role play and creative writing as a useful tool to build resilience in primary school students with and without Special Educational Needs (SEN) in the mainstream classroom. The specific aim of the program was to help students develop a series of fundamental psychosocial skills, such as a positive sense of inner self and the ability to cooperate and relate to others by familiarising with them in recognising and expressing the basic emotions of joy, sadness, fear and anger . Under the systematic cooperation among the general education teacher, the special education teacher and the rest of the teaching staff, the concept was to involve the maximum of the school teachers in order to create a Community of Practice, Collaboration, Sharing Learning and Action. Using an action-based research approach, the data from the present work allowed the participating students to demonstrate a range of socio-emotional skills, including those necessary for self-awareness. Similarly, the teachers involved in the project in each class built positive relations with their students and the rest of the teachers as well, whom they encouraged to participate in various collaborative tasks through similar programs.